2014
DOI: 10.1007/s00213-014-3461-1
|View full text |Cite
|
Sign up to set email alerts
|

Addicted to palatable foods: comparing the neurobiology of Bulimia Nervosa to that of drug addiction

Abstract: Rationale: Bulimia Nervosa (BN) is highly comorbid with substance abuse and shares common phenotypic and genetic predispositions with drug addiction. Although treatments for the two disorders are similar, controversy remains about whether BN should be classified as addiction. Objectives: Here we review the animal and human literature with the goal of assessing whether BN and drug addiction share a common neurobiology. Results: Similar neurobiological features are present following administration of drugs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 171 publications
(244 reference statements)
0
23
0
2
Order By: Relevance
“…This finding is in line with the study by Speranza et al (2012) as it clearly demonstrates that eating behaviour in individuals with BN is highly comparable with substance use in SUDs and that bulimic behaviour may itself be described as an addicted behaviour. These findings based on selfreported behaviour are complemented by recent examinations of neurobiological processes that show similarities between BN and substance dependence as well (Hadad & Knackstedt, 2014).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This finding is in line with the study by Speranza et al (2012) as it clearly demonstrates that eating behaviour in individuals with BN is highly comparable with substance use in SUDs and that bulimic behaviour may itself be described as an addicted behaviour. These findings based on selfreported behaviour are complemented by recent examinations of neurobiological processes that show similarities between BN and substance dependence as well (Hadad & Knackstedt, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…Techniques such as motivational interviewing or acceptance-oriented imagery to cope with urges may be adapted from SUD treatments to enhance motivation to change and dealing with food cravings (Davis & Carter, 2014). Finally, pharmacotherapy targeting opioid and dopaminergic neurotransmitter systems have been shown to be effective in SUD treatments and may also be helpful in reducing binge eating (Davis & Carter, 2014;Hadad & Knackstedt, 2014). For example, a recent animal study showed that an aldehyde dehydrogenase inhibitor, which has been shown to reduce alcohol and cocaine intake in rats, selectively attenuated binge eating of palatable foods and dopamine release in sugar-bingeing rats (Bocarsly et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many theories supported by scientific neurochemical and genetic studies offer sound evidence that food addiction and psychoactive drug addiction are similar (Hadad & Knackstedt, 2014) in spite of arguments to counter this notion (Ziauddeen & Fletcher, 2013). Genetic and epigenetic impairments of the brain reward circuitry, which cause hypodopaminergic functioning, define RDS (Blum et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of data suggests that high-frequency stimulation of the left dorsolateral prefrontal cortex (DLPFC) decreases craving in smoking, alcoholism and cocaine addiction (for review, see Grall-Bronnec et al, 2015;Jansen et al, 2013). BN individuals display aberrant patterns of prefrontal cortex activity during a wide range of experimental task, and BN are assumed to have an addictive component (for review, see Hadad & Knackstedt, 2014). There are also evidences that food craving is associated with DLPFC activity (Kekic et al, 2014), and previous study found that the capacity for self-control depends on DLPFC activity levels (Hare, Camerer, & Rangel, 2009) Thus, it is possible that rTMS of the DLPFC could reduce overeating behaviours by reducing food cravings and by improving cognitive control.…”
Section: Introductionmentioning
confidence: 99%